1998
DOI: 10.1017/s0017089500032754
|View full text |Cite
|
Sign up to set email alerts
|

An operator satisfying Dunford's condition (C) but without bishop's property (β)

Abstract: 1. Introduction. For X a complex Banach space and U an open subset of the complex plane C, let O{U, X) denote the space of analytic X-valued functions defined on U. This is a Frechet space when endowed with the topology of uniform convergence on compact subsets, and the space X may be viewed as simply the constants in O(U, X). Every bounded operator T on X induces a continuous mapping , X) and X e U. Corresponding to each closed F c C there is also an associated analytic subspace X T (F) = XD ran(7c//r). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…In fact, this result could be obtained by combining Theorem 3.1 of [24] and Theorem 10(ii) of [20]. But the proof given in [16] is simple and elegant. Here, we refine this result as follows.…”
Section: Which Unilateral Weighted Shift Operators Have Bishop's Propmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this result could be obtained by combining Theorem 3.1 of [24] and Theorem 10(ii) of [20]. But the proof given in [16] is simple and elegant. Here, we refine this result as follows.…”
Section: Which Unilateral Weighted Shift Operators Have Bishop's Propmentioning
confidence: 99%
“…In [16], T. L. Miller and V. G. Miller have shown that if r 1 (S) < r 2 (S), then S fails Bishop's property (β). In fact, this result could be obtained by combining Theorem 3.1 of [24] and Theorem 10(ii) of [20].…”
Section: Which Unilateral Weighted Shift Operators Have Bishop's Propmentioning
confidence: 99%
“…L'étude de la théorie spectrale locale des opérateurs shiftsà poids scalaires a fait l'objet de plusieurs travaux, on cite par exemple les références [4,13,14,16,17]. Cependant, il apparaît qu'aucuneétude satisfaisante des propriétés spectrales locales d'un shiftà poids opérateurs n'est encore faite.…”
Section: L'adjoint De T Est Défini Parunclassified
“…Dans la dernière section nous complétons et nous généralisons les résultats figurant dans [13]. Nousétablisserons des conditions nécessaires pour qu'un opérateur shift satisfasse la condition de Bishop (β).…”
Section: L'adjoint De T Est Défini Parunclassified
See 1 more Smart Citation